Clinical Profile, Biochemical Alterations, and Therapeutic Outcomes of Jaundice in Pregnant Women. A Clinical Study - Muhammad Kaleem, Hanana Hameed, Muhammad Naveed Najeeb, Sajjad Ul Hasan, Aaisha Qadir5, Maha Sajjad, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Jaundice during pregnancy is a potentially life-threatening condition that can arise from both obstetric-specific and general hepatic disorders. Early recognition is crucial to prevent severe maternal and fetal outcomes. Objective: To assess the clinical profile, biochemical alterations, etiological spectrum, and therapeutic outcomes of jaundice in pregnant women in a tertiary care setting. Methods: A prospective clinical study was conducted at Bolan Medical University Hospital, Quetta, and Mayo Hospital, Lahore, from January 2022 to March 2023. One hundred pregnant women with clinically and biochemically confirmed jaundice were enrolled. Clinical symptoms, laboratory parameters, etiologies, and maternal-fetal outcomes were documented and analyzed. Results: The majority of patients (62%) presented in the third trimester, with multigravidas constituting 61% of cases. Intrahepatic cholestasis of pregnancy (38%) was the most common cause, followed by acute viral hepatitis (26%), HELLP syndrome (20%), and AFLP (16%). Biochemically, all patients exhibited elevated bilirubin levels and transaminases. Severe coagulopathy and hypoalbuminemia were more common in AFLP and HELLP cases. Maternal ICU admission occurred in 14% of cases, and perinatal mortality was recorded at 14%. Preterm delivery occurred in 40%, and 28% of neonates required NICU admission. Conclusion: Jaundice in pregnancy demands timely diagnosis and individualized care to prevent maternal and perinatal morbidity. Enhanced screening, better infection control, and multidisciplinary management are essential in high-burden settings. Keywords: Pregnancy, Jaundice, Intrahepatic Cholestasis, Viral Hepatitis, HELLP Syndrome, AFLP, Perinatal Outcome, Liver Dysfunction in Pregnancy